Mensonge et politique au début de l’âge moderne - Jean-Pierre Cavaillé (Les Dossiers du GRIHL)
The paper addresses the problem of political lie in early modern period. This problem arises from a conflict between the consensual recognition in the political literature of the need of governmental practices of secrecy and deception, and the ethical imposition of an unconditional prohibition of lying by the Christian moral theology under the authority of Augustine of Hippo. We briefly describe the argumentative strategies in order to legitimize orthodox practices of secrecy and deception without lying, and we consider the progressive rehabilitation, on the basis and within the limits of modern natural law, of some practices of lying, for legitimate governmental goals, but also for the protection of the individual rights.